Granitic melt transport and emplacement along transcurrent shear zones : case study of the Pofadder Shear Zone in South Africa and Namibia - Lambert, Christopher William (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.